A comparative morphology of Oscinellinae genera (Diptera: Chloropidae): a framework towards a phylogeny of the subfamily - Bazyar, Zeinab (2019)
The Chloropidae have about 3,000 described species and are often known as grass flies: most members of the family are phytophagous and can be important pests of cereals and cultivated forage grasses. The Chloropidae have been often divided into four subfamilies Siphonellopsinae, Chloropinae, Rhodesiellinae, and Oscinellinae. The oscinellines include 124 genera in the world. This project intends to provide a systematic comparasion of the morphology of the oscinelline genera to test of the monophyly of the subfamily and the monophyly of the Rhodesiellinae, and begin to build a phylogenetic framework for the group. A total of 55 species of 50 genera of oscinellines were used as terminals, with five species of three genera of rhodesiellines, 12 species of 11 genera of chloropines, three species of two genera of siphonellopsines, two species of milichiids and one species of carnid used as outgroups. A total of 167 characters from external adult morphology (head, thorax, wing, legs, and abdomen) and from male and female genitalia have been coded and used to build a data matrix. A phylogenetic analysis was performed to reconstruct the relationships among the taxa using two different analytical parametersimplied weight with k = 3 and a k value (k =~17). Both analyses resulted in one most parsimonius tree, with important differences between them on the position of many genera. The Rhodesiellinae is shown to be paraphyletic in relation to the Oscinellinae, with the Stenoscinini, a rhodesielline tribe, being sister to all remaining Oscinellinae. A large stable clade includes most Fiebriegellini and genera previously included in the Siphonellini, Tricimbini, Oscinisomatini, Liparaini, and Botanobiini. It was corroborated that the Neotropical group blanda of Oscinella does not fit together with the type-species of Oscinella and needs a group of generic rank. A large group of genera belonging to different tribes have no reliable position in the tree, suggesting that the Incertellini, Hippelatini, Oscinellini, and Siphonellini may not correspond to clades. Another large, stable clade (the higher oscinellines) bring together the Dicraeini, and genera of the Botanobiini, Elachipterini, Liparaini, and Hippelatini. Information in the literature gives support to the idea of a clade that gathers these tribes. The use of a considerably large list of characters to analyse a larger generic taxon sampling of the subfamily will certainly help bringing stability to the classification of the group